Digital solutions for Africa’s water management - Velpuri, Naga Manohar; Seid, Abdulkarim; Leh, Mansoor; Mekonnen, Kirubel; Haile, Alemseged Tamiru; Garcia Andarcia, Mariangel; Owusu, Afua; Akpoti, Komlavi; Storr, Samuel; Greatrix, Emma; Wamba, Elizabeth (International Water Management Institute, 2025)
Africa’s water resources are under increasing pressure due to rising demand, climate variability, and declining quality. The Digital Innovations for a Water Secure Africa (DIWASA) initiative, led by IWMI with support from the Helmsley Charitable Trust and in collaboration with Digital Earth Africa, harnesses digital technologies to strengthen water management. By integrating Earth observation, artificial intelligence (AI), and advanced analytics with stakeholder engagement and capacity development, DIWASA provides tools and data to support evidence-based planning and decision-making. This publication showcases DIWASA’s products, partnerships, and applications in countries including Burkina Faso, Ethiopia, Ghana, and Zambia.